2020
DOI: 10.4314/ejhs.v30i2.18
|View full text |Cite
|
Sign up to set email alerts
|

The Burden of Bancroftian Filariasis in Nigeria: A Review

Abstract: BACKGROUND: Lymphatic filariasis (LF) is a neglected tropical disease (NTD) vectored by mosquito; and people in rural areas are mostly at risk of infection. Pooling prevalence data across the six geo-political zones of Nigeria is expected to provide a clearer insight into the burden of the disease as this information could guide towards planning eradication programmes.METHODS: Search for pertinent literature was done on Google Scholar, African Journal Online (AJOL) and PubMed databases using relevant keywords.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 36 publications
1
8
1
Order By: Relevance
“…Contrary to the prevalence rates reported for this infection in other climatic zones of Nigeria which show a high prevalence of 19.2%, 15.8%, and 37%, respectively [15,16], the overall infection in this study is generally low. Perhaps the perception of the people about the disease has improved.…”
Section: Discussioncontrasting
confidence: 99%
“…Contrary to the prevalence rates reported for this infection in other climatic zones of Nigeria which show a high prevalence of 19.2%, 15.8%, and 37%, respectively [15,16], the overall infection in this study is generally low. Perhaps the perception of the people about the disease has improved.…”
Section: Discussioncontrasting
confidence: 99%
“…quinquefasciatus commonly known as the southern house mosquito is widely distributed in tropical and subtropical regions. This opportunistic mosquito has an inherent ability to transmit many diseases including lymphatic lariasis, encephalitis, and west Nile fever (Hussaini et al 2020). In addition, the negative impact on socioeconomic status will further create a serious threat to public health (Rai and Saha, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis that highlighted the changes in the human gut microbiome following treatment with commonly prescribed antibiotics found that return to baseline gut microbiome composition can take from few weeks to several (6+) months. 251 Hence, the increased risk of cardiovascular events after pneumonia that has been demonstrated in clinical studies may, in part, be due to the impact of antibiotic treatment on the gut microbiome and the effect of this phenomenon on cardiovascular disease progression. A recent study of over 37 000 women followed for 28 years found that use of antibiotics in middle and late adulthood was associated with increased cardiovascular risk later in life.…”
Section: Therapeutics For Pneumonia-associated Inflammation: Anti-inf...mentioning
confidence: 99%